Crecimiento, desarrollo y calidad del fruto de la naranja "Victoria" en Jaguey Grande - Alfaro, D.=700 1 Aranguren, M.; Arias, N.; Fajardo, R.; Cruz, P.; Lopez, B.
(Es, En)
Ilus., 23 ref.
Keywords: CITRUS SINENSIS; ETAPAS DE DESARROLLO DE LA PLANTA; FLORACION; MADURACION; FRUTO; CRECIMIENTO; CALIDAD; CUBA; CIENCIA Y TECNICA EN LA AGRICULTURA: CITRICOS Y OTROS FRUTALES